Early events of grapevine resistance towards downy mildew by a systems biology approach - Figueiredo, Andreia (2019)
Grapevine downy mildew, caused by the fungus Plasmopara viticola (Berk. & Curt.) Berl. & de Toni was introduced in European vineyards in the 1870s and quickly spread to all major grape-producing regions worldwide. The early events of grapevine resistance to P. viticola were accessed using transcriptomic, metabolomic and proteomics approaches in the cultivars, ‘Regent' and ‘Trincadeira', resistant and susceptible to downy mildew, respectively. At the transcript level the resistant genotype ‘Regent' presents signalling and defence-related transcripts up-regulated as soon as 6hpi. At the metabolome level, our results show that ‘Trincadeira' and ‘Regent' are intrinsically different as ‘Regent', the resistant cultivar, is able to activate the phenylpropanoid pathway and to accumulate linolenic acid, the precursor of jasmonate in the octadecanoid cascade. At the proteome level ‘Regent' presents upregulated proteins mainly belonging to the functional categories of photosynthesis, carbohydrate metabolism and defence, indicating that this cultivar makes a more efficient use of light, in CO2 assimilation and obtaining intermediate metabolites from photoassimilates for the biosynthesis of secondary metabolites and subsequent defence responses. Our data brings new insights on the molecular processes underlying resistance to Plasmopara viticola, which may eventually enable the design of novel strategies for pathogen control.